Viver a tradição e encontrar a alteridade cultural: investigação fenomenológica na comunidade rural de Morro Vermelho - Roberta Vasconcelos Leite (2011)
From a trajectory of researches in the traditional rural community of Morro Vermelho (MG), we identified the pertinence of analyzing an intercultural encounter in act, as a way to contribute to ongoing debates about the possibilities of contact between cultures. In this research we aimed to investigate how children, raised in a traditional community and who attended the first years of basic education in rural areas, experience the encounter with cultural otherness as they begin to attend school in an urban context. We adopted the Classical Phenomenology (Husserl and Stein) as theoretical and methodological reference. We conducted a brief historical description of the cultural appropriations in Brazilian Social Psychology and we revealed how the phenomenological approach favors the constitution of mutual constitution between subjectivity and lifeworld in the investigation of cultural phenomena. We present how the adopted reference develops fundamental themes for this research: formation of the person in the sociocultural context; tradition as a reference frame and explanatory hypothesis of reality; human maturation and constitutive requests that are the guiding criterion in the multiplicity of alternative actions; opening up to the other and the experience of being a foreigner. To collect data, we conducted an ethnographic participant observation in the rural community of Morro Vermelho and the urban school context during the first week of the school year and we gathered semi-structured interviews with all ten children who had initiated schooling in the city. In the analysis of the intercultural encounter experience - as well as its presentation in this thesis - we sought to preserve the self vitality of the experience. We dug themed contents to grasp the dynamics of the elaboration process in the face of cultural otherness and of the placements in a new sociocultural context. As the results, we documented how children of Morro Vermelho address themselves to school in a culturally diverse environment evaluating everything that presents to themselves, especially what differs from their previous experience, waiting and dedicating to the establishment of new friendships. The transition is experienced as an opening process full of judgments, guided by the need for a totalizing experience of familiarity that children strive to achieve in the new context. Enlightened by this understanding, we retraced previous analyses on the dynamics of the community, being able to evidence how the requirement for total familiarity is a structural factor of the lifeworld of traditional collectivity, which presents itself as a resource in the encounter with the modern society, for it mobilizes the subjects to an open insertion, active and critical. Discussing these results with research in social psychology, we noticed both the originality of this research, as the proximity of our understandings with other researchers. Discussing with investigations about culture, we identified how the tension towards the totality and towards the opening to the otherness, seized in the living experience of the children, articulate themselves to the Brazilian and Baroque cultural features. Our conclusions attested how the demand for totalizing familiarity, characteristic of the traditional formation, may constitute itself as a resource in the intercultural encounters. To reach this understanding, we emphasized the potential of the phenomenological investigation to capture the dynamics of the intercultural encounters, and we highlighted the heuristic value of the concept of tradition, as well as we stressed how the recognition of the demanding character of the experience favors the access to the intimate world-person unit.